Bone Healing Monitoring in Bone Lengthening Using Bioimpedance. (7th April 2022) - Sadoughi, Farahnaz; Behmanesh, Ali; Najd Mazhar, Farid; Joghataei, Mohammad Taghi; Yazdani, Shahram; Shams, Roshanak; Morovvati, Hassan; Najaf Asaadi, Sareh; Vosough, Araz
Abstract : The most common technique of orthopedic surgical procedure for the correction of deformities is bone lengthening by "distraction osteogenesis, " which requires periodic and ongoing bone assessment following surgery. Bone impedance is a noninvasive, quantitative method of assessing bone fracture healing. The purpose of this study was to monitor bone healing and determine when fixation devices should be removed. The left tibia of eight male New Zealand white rabbits (2.4 ± 0.4 kg) undergoing osteotomy was attached with a mini-external fixator. The bone length was increased by 1 cm one week after surgery by distracting it 1 mm per day. Before and after osteotomy, as well as every week after, bone impedance was measured in seven frequency ranges using an EVAL-AD5933EBZ board. Three orthopedic surgeons analyzed the radiographs using the Radiographic Union Scale for Tibial (RUST) score. The Kappa Fleiss coefficient was used to determine surgeon agreement, and the Spearman rank correlation coefficient was used to find out the relationship between impedance measurements and RUST scores. Finally, the device removal time was calculated by comparing the bone impedance to the preosteotomy impedance. The agreement of three orthopedic surgeons on radiographs had a Fleiss' Kappa coefficient of 49%, indicating a moderate level of agreement. The Spearman rank correlation coefficient was 0.43, indicating that impedance and radiographic techniques have a direct relationship. Impedance is expected to be used to monitor fractured or lengthened bones in a noninvasive, low-cost, portable, and straightforward manner. Furthermore, when used in conjunction with other qualitative methods such as radiography, impedance can be useful in determining the precise time of device removal.